Ethylmalonic aciduria is associated with an amino acid variant of short chain acyl-coenzyme A dehydrogenase - Corydon, M. J; Gregersen, N; Lehnert, W; Ribes, A; Rinaldo, P; Kmoch, Stanislav; Christensen, E; Kristensen, T. J; Andresen, B. S; Bross, P; Winter, V; Martinez, G; et al. (Pediatric research, 1996)
Ethylmalonic aciduria is a common biochemical finding in patients with inborn errors of short chain fatty acid beta-oxidation. The urinary excretion of ethylmalonic acid (EMA) may stem from decreased oxidation by short chain acyl-CoA dehydrogenase (SCAD) of butyryl-CoA, which is alternatively metabolized by propionyl-CoA carboxylase to EMA. We have recently detected a guanine to adenine polymorphism in the SCAD gene at position 625 in the SCAD cDNA, which changes glycine 209 to serine (G209S). The variant allele (A625) is present in homozygous and in heterozygous form in 7 and 34.8% of the general population, respectively. One hundred and thirty-five patients from Germany, Denmark, the Czech Republic, Spain, and the United States were selected for this study on the basis of abnormal EMA excretion ranging from 18 to 1185 mmol/mol of creatinine (controls < 18 mmol/mol of creatinine). Among them, we found a significant overrepresentation of the variant allele. Eighty-one patients (60%) were homozygous for the A625 allele, 40 (30%) were heterozygous, and only 14 (10%) harbored the wild-type allele (G625) in homozygous form. By overexpressing the wild-type and variant protein (G209S) in Escherichia coli and COS cells, we showed that the folding of the variant protein was slightly compromised in comparison to the wild-type and that the temperature stability of the tetrameric variant enzyme was lower than that of the wild type. Taken together, the over-representation and the biochemical studies indicate that the A625 allele confers susceptibility to the development of ethylmalonic aciduria.
Keywords: bodová mutace; Cell Line, Transformed; exprese genu; transformované buněčné linie; Gene Expression; RNA, Messenger; vrozené poruchy metabolismu tuků; malonáty; Acyl-CoA Dehydrogenases; vazebná místa; Lipid Metabolism, Inborn Errors; Cercopithecus aethiops; genetická variace; Acyl-CoA Dehydrogenase; Polymorphism, Single-Stranded Conformational; Chlorocebus aethiops; acyl-CoA-dehydrogenasy; polymorfismus konformace jednovláknové DNA; Binding Sites; Animals; Point Mutation; zvířata; Malonates; acyl-CoA-dehydrogenasa; DNA; Genetic Variation; messenger RNA